Pathophysiological mechanisms underlying early brain injury and delayed cerebral ischemia in the aftermath of aneurysmal subarachnoid hemorrhage: a comprehensive analysis - Hendrik Stragier; Hendrik Stragier; Hans Vandersmissen; Sofie Ordies; Steven Thiessen; Steven Thiessen; Dieter Mesotten; Dieter Mesotten; Dieter Peuskens; Hugo Ten Cate; Hugo Ten Cate; Hugo Ten Cate (Frontiers in Neurology)
Early brain injury (EBI) and delayed cerebral ischemia (DCI) are pivotal contributors to morbidity and mortality following aneurysmal subarachnoid hemorrhage (aSAH). Despite advances that have reduced mortality and incidence, aSAH remains a significant public health concern due to its early onset, leading to prolonged periods of diminished quality of life for affected individuals. EBI mechanisms, including endothelial dysfunction, blood–brain barrier disruption, cerebral edema, neuro-inflammation, cortical spreading depolarizations, and oxidative damage, trigger cell death and apoptosis, setting the stage for DCI development in later clinical phases. DCI arises not only from large-vessel vasospasm, but also from other complex pathophysiological processes, including thrombo-inflammation, neuro-inflammation, microcirculatory dysfunction, and glycocalyx disruption. Recognizing and understanding these mechanisms is essential, as early interventions could potentially reduce long-term disability in this population. This comprehensive review offers an in-depth analysis of these pathophysiological mechanisms. As our understanding of these processes continues to evolve, further research is crucial to improving outcomes and reducing the long-term impact of aSAH.